An Evaluation of the Association of Reproductive History and Multiple Births during Adolescence with Postmenopausal Osteoporosis - Kaya, Aski Ellibes; Doğan, Ozan; Başbuğ, Alper; Sönmez, Cemil Işık; Sungur, Mehmet Ali; Ataoğlu, Safinaz (Geburtshilfe und Frauenheilkunde, 2019)
Introduction Osteoporosis is the most common metabolic bone disease characterized by low bone mass. Reproductive factors are known to affect bone mineral density (BMD). Calcium loss from maternal bone and decreased BMD have been observed especially during pregnancy and lactation, although this loss has been reported to recover within 6 – 12 months. There is no consensus on whether the effect of reproductive factors on the bone is positive or negative. The adolescent period is important for total bone mass, and total bone mass is significant in osteoporosis. The aim of this study was to investigate the effect of first gestational age, multiple births during adolescence, interpregnancy interval and reproductive history such as duration of breastfeeding on bone mineral density in postmenopausal women.Materials and Methods BMD was measured in a total of 196 postmenopausal patients and in accordance with the results, analysis was made of three groups as normal, osteopenia and osteoporosis. Dual Energy X-Ray Absorptiometry (DEXA) was used to take the lumbar, femoral and total bone BMD measurements.Results No statistically significant difference was determined between the groups in respect of total breastfeeding time (p = 0.596). It was detected that an increased interpregnancy interval decreased the risk of osteoporosis. In patients with osteoporosis, the mean interpregnancy interval was 1.4 ± 0.73 years, while it was longer in patients with osteopenia (1.92 ± 1.20) and normal BMD (2.45 ± 1.77) (p = 0.005). While no effect was determined of the first gestational age on BMD, in the univariate logistic regression analysis, multiple births in the adolescent period were seen to increase the risk of osteoporosis 6.833-fold (p = 0.001, OR = 6.833, 95% CI = 2.131 – 21.908; p = 0.001). The increase in the age of menopause was determined to decrease the risk of osteoporosis (OR = 0.911, 95% CI = 0.843 – 0.985; p = 0.019).Conclusion Having frequent births throughout the whole reproductive age and having more than one child in adolescence has an adverse effect on postmenopausal bone mineral densities.
Keywords: adolescent; breastfeeding; bone mineral density; postmenopausal osteoporosis; interpregnancy interval